Short Review of the Current Value of Pharmaceutical Care for Patients – A Patient Survey about Single Beliefs, Concerns, and Expectations to Public Pharmacies - Schlieper, Valentin (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2022)
In a world that gets more and more digitalized, people and therefore in general patients feel more and more safe to use digital applications. In the pharmacy, digitalization could become either disruptive or a lifeline for the future. Pharmaceutical care (PC) is a main point in the pharmacy that could be digitalized. The goal of this short study is to evaluate how patients perceive the performance of local pharmacies efforts toward good PC including digital influences. A patient survey about single beliefs, concerns, and expectations toward various services in public pharmacies was done. To see the current state of digital PC management in three pharmacies in Germany, 200 patients were questioned. Our focus was based on the five main principles of PC defined by the American Pharmacists Association. The results of the survey lead pharmacists toward the direction in which they should focus their digital PC management. Patients agreed on the importance of PC in general. They advocate the professional advice on therapy management but also criticize the management of their personal health data. They have expectations that could be fulfilled with digital solutions to fully satisfy their wish of personal PC. We can say that even though there is a lot of potential toward the health data management, the 200 patients are overall satisfied with the current form of mostly non-digital PC in public pharmacies. The results of the survey lead pharmacists toward the direction in which they should focus their digital PC management in the future to achieve even better approaches in PC.